Censo de aves migratórias (Charadriidae, Scolopacidae e Laridae) na Coroa do Avião, Igarassu, Pernambuco, Brasil - Telino-Júnior,Wallace R.; Azevedo-Júnior,Severino M. de; Lyra-Neves,Rachel M. de (Sociedade Brasileira de Zoologia, 2003)
Thousands of shorebirds and seabirds use the Atlantic route through the northeastern coast of Brazil every year to migrate to South America. In this study was made a census of individuals that uses the Coroa do Avião (7º40'S and 34º50"W), an islet located on the south bar of the Santa Cruz channel on the north coast of Pernambuco state, from May 1993 throughout April 1995 and from August 1996 throughout July 1997. Four species of the family Charadriidae, seven species of the family Scolopacidae, and two species of the family Laridae was observed. The populational peaks match both the period of arrival to the winter season site and the period of departure to the reproduction site. The species considered very frequent were: Charadrius semipalmatus Bonaparte, 1825 and Calidris alba (Pallas, 1764). All the other species were considered rather frequent. There was a strong linear correlation between 1993 and 1994 among Pluvialis squatarola (Linnaeus, 1758) and Arenaria interpres (Linnaeus, 1758); A. interpres and Calidris pusilla (Linnaues, 1766); A. interpres and C. alba; and C. pusilla and C. alba. From 1994 to April 1995 it occured between P. squatarola and C. alba; C. semipalmatus and C. pusilla; C. semipalmatus and C. pusilla; and A. interpres and C. pusilla. From August 1996 throughout July 1997 there was correlation only between P. squatarola and C. pusilla. The obtained results demonstrate the great importance of the Coroa do Avião as a winter season site.